Kajian Implementasi Rekruitmen Pejabat Struktural Pada Jabatan Karir Pegawai Negeri Sipil di Kabupaten Bolaang Mongondow Utara - Tabo, Sarfan; rumapea, patar (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Absrtact: The purpose of this study was to describe, analyze, and interpret: 1). Competencies and skills of structural, 2). Recruitment process of structural, 3). Constraints encountered in implementation of the recruitment of structural. This study is a qualitative research through observation, interviews and documentation. Methods of analysis was performed by qualitative data analysis techniques. The results show that the competence and expertise possessed by each employee was still low, because of most the Class III employees were recruited, but was dominated by the functional employee, such as teachers, doctors and nursing. There were some positions to be filled in the structural level that have not been occupied, because no employees were eligible for the positions, particularly with respect to rank. In addition, the competence of the recruited employees, have not been met. However, when viewed from the other side, that the authority is generally performed when a person who occupies a particular position can not afford to run a good job, so the Government Regulation No. 9 of 2003 can be implemented. This has been one of the Regents authority. It can be concluded that there were three major obstacles in the implementation of structural recruitment of officials in the District of North Bolaang Mongondow, namely human resources, conditions of employment facilities, and work programs that provide such a huge impact on the performance of the institution. North Bolaang Mongondow Regency has limited capacity of the division of human resources that are competent, ie the number of local government officials that were recruited were not based on the analysis of the needs of each Unit (SKPD), and also the competence and skills did not become the main consideration in the recruitment process. It is thus recommended to optimize the process of recruiting officials in North Bolaang Mongondow Regency necessary to optimize the implementation of Government Regulation No. 13 of 2003, as well as provide input to the head area as the party's decision to give a person to occupy certain positions. Key Words:The Recruitment in the Bureaucracy Structural Post, Officer Resource Development